In situ control of graphene ripples and strain in the electron microscope - Ludacka, U.; Monazam, M. R. A.; Rentenberger, Christian; Stefanelli, Ulisse; Meyer, J. C.; Kotakoski, Jani; Friedrich, Manuel (npj 2D Materials and Applications, 2018)
We demonstrate control over the three-dimensional (3D) structure of suspended 2D materials in a transmission electron microscope. The shape of our graphene samples is measured from the diffraction patterns recorded at different sample tilts while applying tensile strain on the sample carrier. The changes in the shape of the pattern and in individual diffraction spots allow us to analyze both corrugations and strain in the lattice. Due to the significant effect of ripples and strain on the properties of 2D materials, our results may lead to new ways for their engineering for applications.
CRIS-Team Scopus Importer:2021-10-21